Upravljanje območij s kulturno dediščino - Nared, Janez; Razpotnik Visković, Nika (CAPAcities, 2014)
Managing Cultural Heritage AreasComprehensive planning for cultural heritage areas must bring together social, cultural, economic, transport, and environmental aspects and promote active inclusion of various, and even conflicting, interest groups in a guided participatory process. In order for managers of such areas to best equip themselves with useful information, this book presents various topics that are important from the perspective of cultural heritage management: classification of cultural heritage, the role of UNESCO and its guidelines in protecting cultural heritage, and theoretical views on cultural heritage preservation. This is followed by a planning section, which presents environmental planning in areas with cultural heritage, the role of cultural heritage and protecting it, revitalization of old urban cores, and restoration of historical buildings and town centers.